PARTISIPASI MASYARAKAT PADA PEMILU LEGISLATIVE TAHUN 2019 DI DESA TAMBOO KECAMATAN TILONGKABILA KABUPATEN BONE BOLANGO - GANI, MOHAMMAD TRIYADI SAPUTRA; LENGKONG, FLORENCE DAICY; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2019)
The research aims to determine the participation of the community in the election legislative year 2019 inthe village Tamboo District Tilongkabila Bone Bolango Regency. This research uses a type of qualitativedescriptive research. The focus of this research is to know the community participation in the village ofTamboo District Tilongkabila Bone Bolango in the vote in the election legislative year 2019 which includesElectrolaral Activity, Lobbying, Organizational Activity, Contacting, and Violance. The informant in thisresearch is the community of Tamboo village which amounted to 10 people, which is taken from all elementsof society (8 people) and also local village government (2 people). The data sources in this study are primarydata and secondary data. Research data collection techniques using observation methods, interviews, datacollection with documents. The results showed that the community participation rate in the 2019 legislativeelections in Tamboo village was reviewed from electrolaral activity, lobbying, organization activity,contacting, and violence showed that it has been very good Because of the thought of the communityrational voters.Keyword : Community participation, Legislative elections